Transforming Tribal Women’s Lives through Education: Integrating Cultural Relevance, Skill Development, and Gender-Focused Strategies (International Journal of Scientific Research in Science and Technology, 2025)
This paper explores the transformative role of education in empowering tribal women by integrating culturally relevant knowledge systems, gender-sensitive strategies, and skill-based initiatives. Grounded in empowerment and capability theories, the study employs a structured literature review and qualitative synthesis of secondary sources and case-based evidence. The review identifies persistent challenges such as socio-cultural restrictions, economic disadvantages, and infrastructural deficiencies that continue to limit educational access for tribal women. It further examines interventions that have demonstrated positive outcomes, including mother-tongue instruction, community participation, targeted financial support, and vocational as well as digital literacy programs. The analysis highlights that when these measures are implemented in combination, they not only improve educational access and retention but also expand women’s agency across economic, social, and political domains. The study concludes with policy recommendations for scaling context-specific interventions and suggests directions for future empirical research to sustain empowerment through education.